Nannoplankton community across a shelf transect during the onset of the Paleocene-Eocene Thermal Maximum - León y León, Isabel A; Bralower, Timothy J; Self-Trail, Jean (Supplement to: León y León, IA et al. (2018): Ecological changes in the nannoplankton community across a shelf transect during the onset of the Paleocene-Eocene Thermal Maximum. Paleoceanography and Paleoclimatology, https://doi.org/10.1029/2018PA003383, 2018)
Warming and other environmental changes during the Paleocene‐Eocene Thermal Maximum (PETM) led to profound shifts in the composition and structure of nannoplankton assemblages. Here we analyze the nature of these changes in expanded records from the Cambridge‐Dorchesterand Mattawoman Creek‐Billingsley Road cores in Maryland. These cores comprise part of a transect of five paleoshelf cores from Maryland and New Jersey. We integrate multivariate analysis of assemblage data with proxy data to revise understanding of the paleoecological affinities of key species. In particular, Discoaster and Fasciculithus are interpreted as thermophiles without adaptation to particular nutrient levels, while Hornibrookina is considered an opportunist adapted to highly variable nearshore environments. Together the cores show consistent margin‐wide changes across the onset of the PETM, including a pulse of pre‐event warming, possibly combined withlower salinity, high seasonality, or increased turbidity. The event itself was characterized by continued warming and eutrophication across the paleoshelf. The Maryland sites experienced higher environmental variability as a result of their proximity to large river systems.